G493 How can health services effectively improve the mental health of young people leaving public care? the lync study. (27th April 2015) - Butterworth, SJ; Islam, Z; Vostanis, P; Munro, E; Paul, M; Birchwood, M; Singh, S; Khan, A; Simkiss, D
Abstract : Aim: To explore the mental health needs and service use of young people transitioning out of local authority care. Methods: A mixed-method study in one local authority. Qualitative methods included a thematic analysis of interviews with 12 care leavers with an identified mental health need and 12 relevant staff members from across the agencies involved with young people. Quantitative methods for analysing transition included screening social care and health service notes from age 15 of 40 care leavers aged 18–22 years. Analysis documented the completeness of pathway planning (adherence to national guidance), identified mental health needs (diagnoses, service involvement) and the effectiveness of CAMHS to AMHS transition (information continuity, joint working, transition planning and continuity of care). Results: Qualitative analysis of care leaver interviews generated four superordinate themes: overarching attitudes towards the care journey, experience of social care, experience of mental health services and recommendations. Qualitative analysis of staff interviews produces six superordinate themes: young people's lives, the transition process, system failure, professionals' understanding of mental illness, inter-agency working, capacity and limited service. Initial quantitative analysis showed that during transition young people were very mobile, expressed high mental health needs and accessed multiple mental health services with a high rate of crisis pathways. Data on the quality of transition will be analysed in December 2014 and will be available for presentation at the ASM. Conclusion: Care leavers with mental health problems face many transitions and felt abandoned with a poor experience of services during this time. Staff said transitions were often poorly delivered with care leavers ill-equipped to manage. They said that inter-agency working was weak, without a shared protocol or information sharing or a collaborative approach to care. Recommendations for improving transition include joint commissioning across the transition period, continuity between child and adult services, staff training, care-leavers active involvement, identification and evaluation of best practice models. Further research is needed to develop and rigorously evaluate models of transitional care that promote mental health and wellbeing.